PEMBELIAN IMPULSIF DAN PENGELOLAAN KEUANGAN MAHASISWA: (BUKTI EMPIRIS DARI PROGRAM STUDI MANAJEMEN UNIVERSITAS PERSATUAN GURU 1945 NTT) - Yunita Elisabeth Taniu; David R E Selan; Jhon D. S Liem (P3M Politeknik Negeri Ambon, 2026)
This study aims to examine the effect of impulsive buying on the financial management of students in the Management Study Program, Universitas Persatuan Guru 1945 NTT. Effective financial management is essential for students to manage their financial resources wisely and support responsible financial decision-making. This study employed a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to students of the 2022 cohort, while secondary data were obtained from relevant literature and institutional documents. The data were analyzed using simple linear regression to examine the effect of impulsive buying on students' financial management. The results show that impulsive buying has a significant effect on students' financial management, as indicated by the regression equation Y = 20.781 − 0.072X. The correlation analysis yielded a coefficient of r = 0.87, indicating a very strong relationship between the variables. Furthermore, the coefficient of determination (R² = 75.69%) indicates that impulsive buying explains 75.69% of the variation in students' financial management, while the remaining 24.31% is explained by other factors outside the scope of this study. These findings suggest that understanding impulsive buying behavior is important in improving students' financial management and encouraging more responsible financial decision-making. Keywords: impulsive buying; financial management; university students; consumer behavior; personal finance.